Investigation of Forest Fire Effects on Morel (Morchella spp.) Mushroom Proliferation: A Case Study of Alucra, Giresun - Bülent Sağlam; Mustafa Aybar; Fatma Nur Yılmaz (Doğal Afetler ve Çevre Dergisi)
After each forest fire, which are effective in thousands of hectares of land every year in Turkey, many new plant species appear in burning areas and many animals start browsing on these areas. Likewise, it is known that many mushroom species intensely emerge in the area after each fire. Among these species, some species of Morel mushrooms (Morchella spp.), which are consumed all around the world despite their high price. For that reason, it is a very high potential income source for the local forest villagers. Some kinds of Morel mushroom species emerge abundantly in burnt areas after forest fires due to sudden changes in soil chemistry and ash accumulation after the burns of small branches and lives. The aim of this present study is to determine Morel mushroom proliferation growth potential after burnt of forested land based on the soil pH and organic matter. Our results showed that together with the fire, the soil pH and accompanying organic matter increased and therefore proliferation of the morel mushroom increased. The soils that the mushroom was not detected on have either high pH value and low organic matter or high organic matter and low soil pH value alone. A high soil pH and high organic matter should be presented at the site together. The average organic matter and pH values of the area which including mushroom exposed to forest fire were found to be 7.25 and 6.71 respectively while the average organic matter and pH values of the unburned forested area showing same ecological characteristics were found to be 5.65 and 5.98. We conclude that forest fires, one of the most important natural disasters that cause damage in the forests, can also be used within the scope of morel mushroom production. Income from mushroom production in the burnt areas will boost the income of local forest villagers and make an additional financial relief into their limited annual budgets.